Techno-Economics Analysis for The Yogurt Business Development for Mustahik of Productive Zakat - Purnamasari, Lise; Warizal, W.; Suherman, Irman (ASEAN Journal of Science and Engineering, 2026)
The purpose of this study was to analyze the feasibility studies on the production of yogurt from raw materials of pure milk, sugar, flavor, and the addition of lactobacillus. We conducted the techno-economic analysis, which can be used by zakat mustahik for 20 years, including Total Investment Cost (TIC), Gross Profit Margin (GPM), Internal Rate of Return (IRR), Payback Period (PBP), Cumulative Net Present Value (CNPV), Break Even Point (BEP) and sales ratio to investment. The results of the study show that the CNPV/TIC analysis is a graph that tends to increase although not significantly in each period, the project in an ideal time of 20 years. This illustrates that Yogurt production is very prospective because it shows the feasibility of a profitable project. Yogurt entrepreneurs from productive zakat can support the main program of productive zakat, namely mustahik becoming muzakki in the future. The impact of this study is to provide an estimate of yogurt production as a prospective business unit for productive zakat mustahik.